Analisis Manajemen Kas Negara Masa Khulafaur Rasyidin dan Sentralisasi Birokrasi Keuangan Masa Dinasti Abbasiyah: Analysis of State Cash Management in the Era of Guided Caliphate and the Centralization of Financial Bureaucracy in the Abbasid Dynasty - Mia Novi Rahmawati; Kyara Namira Rinjani; Lina Marlina; Ana Fauziya Dinaya (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2026)
This study addresses the limited integrative analysis in Islamic public finance by explicitly identifying a conceptual research gap in the disconnection between cash management systems and financial bureaucracy frameworks by examining the evolution of state cash management and financial bureaucracy during the Khulafaur Rasyidin and Abbasid periods. It aims to analyze how differing fiscal governance models emerged as adaptive responses to changing state complexity. This research employs a qualitative approach using comparative historical analysis and historical content analysis based on Ibn Khaldun’s State Evolution Theory. The methodological approach is designed to systematically compare institutional structures, fiscal mechanisms, and oversight systems across historical periods. Data are derived from classical Islamic texts and recent scholarly literature to ensure both historical depth and contemporary relevance. The findings reveal two distinct fiscal paradigms. The Khulafaur Rasyidin period implemented a flow-based fiscal system characterized by a zero-reserve policy that prioritized rapid wealth distribution. In contrast, the Abbasid period developed a stock-based fiscal system through institutionalized financial bureaucracy (Diwan) and layered auditing mechanisms to support fiscal sustainability and administrative complexity. This transformation reflects institutional adaptation rather than normative decline. The study contributes by proposing a hybrid fiscal governance model that integrates high-velocity distribution with multi-layered accountability. This contribution not only bridges historical and modern governance frameworks but also provides a transferable analytical model for contemporary fiscal policy design.